FRAGMENTASI OTORITAS INTERPRETATIF PENGHULU DALAM PRAKTIK TAKLIK TALAK KONTEMPORER : STUDI KASUS DI KOTA PALANGKARAYA - Aris Sunandar Suradilaga; Tiara Salsabila; Eka Suriansyah; Akhmad Kamil Rizani (LPPM STAI Muhammadiyah Probolinggo, 2026)
This study examines the fragmentation of marriage registrars’ interpretive authority regarding the omission of the oral recitation of the ṣīghat taklik talak in contemporary marriage ceremonies in Palangka Raya and its implications for the protection of women’s rights. Using an empirical legal method with a socio-legal approach, data were collected through interviews, observations, and documentation involving marriage registrars from several Offices of Religious Affairs (KUA) and analyzed qualitatively. The findings reveal differing views among marriage registrars. Some consider the oral recitation of the ṣīghat taklik talak a quasi-obligatory practice that functions as legal education and a safeguard for wives’ rights, while others argue that signing the taklik talak document in the marriage certificate is sufficient to fulfill legal requirements. The omission of oral recitation is influenced by time constraints, limited legal literacy, and cultural perceptions that regard the mention of divorce (talak) on the wedding day as taboo. Although this practice does not affect the validity of marriage, it may weaken legal awareness and reduce the protective function of taklik talak for women. Theoretically, the findings reinforce socio-legal perspectives and the relevance of maṣlaḥah mursalah in understanding the preventive role of ṣīghat taklik talak. Practically, the study highlights the need to strengthen premarital legal literacy and standardize marriage services within KUA institutions